The terminological meaning of the expressions “clergyman,” “cleric,” and “religious person” under Polish state law. Remarks from the perspective of the practical application of the law in relation to the major religious systems of the world - Grabowski, Mariusz (Prawo Kanoniczne, 2023)
In common understandings, a "clergyman" is a "more important" member of a given religious community, due to his position in this community. This position results from holding a specific office or function in a religious community. Understood in this way, the clergyman differs from other "ordinary" or "secular", i.e. non-spiritual members of the community. The concept of a clergyman is not defined in state law. The exception is such legal systems in which we are dealing with the sacralization of the law. In the latter case, the state law also contains religious norms. In the first situation, the state law refers to the definition of a clergyman contained in the law of a religious community recognized by the state (church, religious association). In the second situation, the definition of "clergyman" is included in state law and is usually transferred from the law of a religious community. It can be assumed that a "clergyman" is a person whose status results from the provisions of the law of a given church or religious association.